Anti-populist populism: Musical challenges to Trump's America and Erdoğan's Turkey. Issue 3 (October 2022) - Way, Lyndon C.S.
Abstract: Populism is a discursive construct that represents popular interests and values by 'pretend[ing] to speak' for the people who are constructed separate and opposed to a powerful elite. Yet populism, in its various forms and accents, 'can adapt flexibly to a variety of substantive ideological values and principles'. This is manifested in 'the people' not being a prefixed natural category, but a signifier that acquires meaning through discourses and contexts. This article considers how populism is articulated in hip hop videos that criticise two authoritarian-populist politicians: America's Trump and Turkey's Erdoğan. Using Multimodal Critical Discourse Studies, Eminem's 'The Storm' and Ezhel's 'Yarınımız Yok (We have no tomorrow)' are analysed to demonstrate how oppositional popular music can articulate its own brands of populism, transcending contexts, yet shaped by them.